Identification of Two Novel Peptides That Inhibit α-Synuclein Toxicity and Aggregation - Popova, Blagovesta; Wang, Dan; Rajavel, Abirami; Dhamotharan, Karthikeyan; Lázaro, Diana F.; Gerke, Jennifer; Uhrig, Joachim F.; Hoppert, Michael; Outeiro, Tiago F.; Braus, Gerhard H. (Frontiers in Molecular Neuroscience, 2021)
Aggregation of α-synuclein (αSyn) into proteinaceous deposits is a pathological hallmark of a range of neurodegenerative diseases including Parkinson’s disease (PD). Numerous lines of evidence indicate that accumulation of toxic oligomeric and prefibrillar αSyn species may underpin the cellular toxicity and spreading of pathology between cells. Therefore, aggregation of αSyn is considered a priority target for drug development, as aggregation inhibitors are expected to reduce αSyn toxicity and serve as therapeutic agents. Here, we used the budding yeast S. cerevisiae as a platform for the identification of short peptides that inhibit αSyn aggregation and toxicity. A library consisting of approximately one million peptide variants was utilized in two high-throughput screening approaches for isolation of library representatives that reduce αSyn-associated toxicity and aggregation. Seven peptides were isolated that were able to suppress specifically α-synuclein toxicity and aggregation in living cells. Expression of the peptides in yeast reduced the accumulation of αSyn-induced reactive oxygen species and increased cell viability. Next, the peptides were chemically synthesized and probed for their ability to modulate αSyn aggregation in vitro. Two synthetic peptides, K84s and K102s, of 25 and 19 amino acids, respectively, significantly inhibited αSyn oligomerization and aggregation at sub-stoichiometric molar ratios. Importantly, K84s reduced αSyn aggregation in human cells. These peptides represent promising αSyn aggregation antagonists for development of future therapeutic interventions.